Tensile examination of progressive damage and failure in porous ceramic composite materials using the XFEM - Metehri, Aicha; Madani, Kouider; Mechab, Belaïd; Mokhtari, Mohammed; Ghermaoui, Ilias M.A. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: Porosity is a significant factor that causes voids to become trapped in materials during composite material fabrication. This study is dedicated to modelling fracture modes within highly stressed areas of an advanced SiC/Cf component at a macroscopic scale.Methods: The finite element method is used to analyze defects within composites, considering factors such as porosity size, shape, and tensile stress. The Monte Carlo method predicts the distribution function (F).Results: Three pores are distributed across the width of the material, which reduces the active cross-sectional area of the material and, consequently, leads to a significant reduction in strength. Overall, resistance tends to decrease, with a more noticeable drop.Conclusion: It is concluded how the form and the size affect the failure load, employing the Extended Finite Element Method (XFEM) to predict mode-I fracture behaviour. The porosity parameter significantly affects the durability of the structure. It is noted that the size of pores (ϕ) is a crucial component that affects the distribution function (F). The variability in this parameter substantially elevates the likelihood of plate failure and diminishes the  longevity of a structure.
Keywords: composite; XFEM; tensile load; failure load; fibre reinforced; size